2021
DOI: 10.1287/mksc.2021.1296
|View full text |Cite
|
Sign up to set email alerts
|

“Meet Me Halfway”: The Costs and Benefits of Bargaining

Abstract: Bargaining is an important pricing mechanism, prevalent in both online and offline markets. However, there is little empirical work documenting the costs and benefits of bargaining, primarily because of the lack of real-world bargaining data. We leverage rich, transaction-level bargaining data from a major online platform and supplement it with primary data to quantify the costs and benefits of bargaining for sellers, buyers, and the platform. We do this by building a structural model of buyer demand and selle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Another consideration is hybrid pricing, such that sellers post a price but also negotiate with consumers (e.g., Chen and Rosenthal 1996;Cui, Mallucci, and Zhang 2019;Desai and Purohit 2004;Gill and Thanassoulis 2016;Riley and Zeckhauser 1983;Zeng, Dasgupta, and Weinberg 2014). According to contributions in this research stream, competition (Huang 2020;Zhang, Manchanda, and Chu 2021), the fixed costs of initiating a negotiation (Jindal and Newberry 2018), cognitive dissonance, and sunk cost fallacy (Desai and Jindal 2021) all influence the profitability of a hybrid pricing strategy. My goal is not to compare the profitability of pricing strategies, though I explore and clarify the retailer's incentive to set an exaggerated ARP under bargaining, and I establish the profit implications of posting an optimal ARP for different pricing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another consideration is hybrid pricing, such that sellers post a price but also negotiate with consumers (e.g., Chen and Rosenthal 1996;Cui, Mallucci, and Zhang 2019;Desai and Purohit 2004;Gill and Thanassoulis 2016;Riley and Zeckhauser 1983;Zeng, Dasgupta, and Weinberg 2014). According to contributions in this research stream, competition (Huang 2020;Zhang, Manchanda, and Chu 2021), the fixed costs of initiating a negotiation (Jindal and Newberry 2018), cognitive dissonance, and sunk cost fallacy (Desai and Jindal 2021) all influence the profitability of a hybrid pricing strategy. My goal is not to compare the profitability of pricing strategies, though I explore and clarify the retailer's incentive to set an exaggerated ARP under bargaining, and I establish the profit implications of posting an optimal ARP for different pricing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Consumer Reports (Rechtin 2016), 70% of all used car buyers negotiated the price, and 83% were able to bargain a lower price. Similarly, Jindal and Newberry (2021) find negotiated prices for more than 90% of purchases in their data, and Zhang, Manchanda, and Chu (2021) indicated that 80% of mobile phone sellers allow for negotiated discounts on Taobao.com. 2 In turn, negotiations have become more common for less expensive products, such as collectibles, sports memorabilia, clothing, toys, and books, such that online retailers often list two different prices (see the bottom panel in Figure 1).…”
mentioning
confidence: 95%
“…Ironically, even markets that are traditionally considered venues for haggling, such as automobile buying, are responding to buyers' proclivities, and offering more fixed price options. As Jindal and Newberry (2018) and Zhang et al (2021) point out, when buyers are known to have heterogeneous intentions to negotiate, it becomes important for firms to offer hybrid and flexible price-setting mechanisms to maximize sellers' utility.…”
Section: Introductionmentioning
confidence: 99%
“…Past research informs us that negotiation is an important tactic that can benefit both buyers and sellers in B2C markets. Findings from research suggest that negotiation can yield positive economic utility for both buyers and sellers (Holmes et al , 2017; Jindal and Newberry, 2018; Zhang et al , 2021). In addition, buyers who invoke a play orientation also accrue hedonic utility from negotiation (Dawra et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation